A Rapid and Efficient Way to Dynamic Creation of Cross‐Reactive Sensor Arrays Based on Ionic Liquids. Issue 35 (19th July 2013) - Zhu, Wei; Li, Weina; Yang, Haowei; Jiang, Yin; Wang, Chen; Chen, Yu; Li, Guangtao
Abstract Based on the simple counterion exchange of ionic liquids, a rapid, facile, and efficient strategy to create a cross‐reactive sensor array with a dynamic tunable feature was developed, and exemplified by the construction of a sensor array for the identification and classification of nitroaromatics and explosives mimics. To achieve a good sensing system with fast response, good sensitivity, and low detection limit, the synthesized ionic liquid receptors were tethered onto a silica matrix with a macro‐mesoporous hierarchical structure. Through the facile anion exchange approach, abundant ionic‐liquid‐based individual receptors with diversiform properties, such as different micro‐environments, diverse molecular interactions, and distinctive physico‐chemical properties, were easily and quickly synthesized to generate a distinct fingerprint of explosives for pattern recognition. The reversible anion exchange ability further endowed the sensor array with a dynamic tunable feature as well as good controllability and practicality for real‐world application. With the assistance of statistical analysis, such as principal component analysis (PCA) and linear discrimination analysis (LDA), an optimized‐size array with a good resolution was rationally established from a large number of IL‐based receptors. The performed experiments suggested that the ionic‐liquid‐based sensing protocol is a general and powerful strategy for creating a cross‐reactive sensor array that could find a wide range of applications for sensing various analytes or complex mixtures.